TINDAK TUTUR MENOLAK DALAM BAHASA JEPANG DAN BAHASA INDONESIA: KAJIAN KONTRASTIF - Gustini, Maria (2016)
Tindak tutur menolak merupakan salah satu tindakan yang bisa memberikan perasaan tidak menyenangkan terhadap lawan tutur. Tindak tutur menolak dilatarbelakangi oleh hubungan vertikal (jouge kankei) maupun hubungan kedekatan (shinso kankei) antara penutur dan lawan tutur. Penelitian ini bertujuan untuk mendeskripsikan perbandingan tindak tutur menolak dalam bahasa Jepang dan bahasa Indonesia di lingkungan kerja berdasarkan hubungan antara pembicara dengan lawan bicara (jouge kankei dan shinso kankei). Penelitian ini menggunakan metode penelitian deskriptif dengan instrumen Discourse Completion Test (DCT). Adapun objek penelitiannya terdiri dari 80 orang (40 orang penutur asli bahasa Indonesia dan 40 orang penutur asli bahasa Jepang). Berdasarkan analisis data dapat diketahui beberapa persamaan dan perbedaan strategi yang digunakan oleh penutur asli bahasa Indonesia dan bahasa Jepang di lingkungan kerja. Secara umum penutur bahasa asli Indonesia (IS) dan penutur asli bahasa Jepang (JS) menggunakan strategi {wabi}, {riyuu}, dan {fuka} sebagai strategi utama dalam penolakan. Namun terdapat beberapa strategi yang tidak digunakan oleh JS diantaranya {koshou} dan {kantoushiteki hyoutsutsu} dalam penolakan terhadap atasan akrab dan teman akrab. Dalam penggunaan {riyuu} IS cenderung menggunakan alasan yang konkrit dan bervariasi sedangkan JS menggunakan alasan yang samar. Selain itu, terdapat penggunaan strategi baru yang tidak muncul dalam penelitian sebelumnya yaitu dalam penolakan terhadap bawahan yaitu {meirei} yang digunakan oleh reponden IS maupun JS. Dilihat dari strategi kesantunan menurut Brown&Levinson (1987) strategi penolakan yang dipakai oleh IS cenderung menggunakan kesantunan positif sedangkan JS cenderung menggunakan strategi kesantunan negatif. Kata kunci: kotowaru, penolakan, strategi kesantunan, lingkungan kerja This article examines Contrastive Analysis of Refusal in Indonesian language and Japanese language. Refusing act is not easy thing because it is an act which directly threatens the listeners or Face Threatening Act. Refusing the request or command from interlocutors means not granting the wishes of what the opponents said. It somehow caused the imbalance relationship between the speaker and interlocutor so that a specific strategy is required when conducting refusal act. Cultural background differences between native and foreign-language speakers can sometimes be the factor of unbalance and disharmonious communication within the language. Refusals are the major cross-cultural "sticking point" for many non-native speakers, and for that reason it is important for second language educators and others to involve in cross cultural communication. Up to now, there have been no contrasive researchs which compare refusal speech acts within Indonesian language and Japanese language, focused on working situations. In general, researchers simpy examined the refusing act in the contexts of education among Japanese language learners. This article reports on a study to investigate differences and similarities in the politeness strategies of refusals between Japanese language (JS) and Indonesian language (IS). This study employed politeness theory of Brown and Levinson (1987). Subject of this research focused on refusal in working situations. Therefore the participants of this reseach were Indonesian and Japanese who currenly work in company, shchool, etc. This research didn't involve student who learn Japanese language. This research used descriptive method and collecting data using DCT (Discourse Completion Test) in Indonesian and Japanese. Before conducting this research, I did preliminary research. Therefore, the research subjects in this study were those who already worked with the age-range from 22 to 50 years. 80 employees participated in this study: 40 native speakers of Indonesian (IS) and 40 native speakers of Japanese (JS). All participants were asked to fill out a Discourse Completion Test (DCT) which written in the form role-play questionnaire, consisting of 3 situations. Each situation contained a blank in which only refusal would fit. The directions were written out on the DCT. DCT situations were categorized based on power and familiarity/social distance between speaker and hearer. Upon comparing the politeness strategies of the whole refusal used by JS and IS in each situation, qualitative differences were found between the frequency of politeness strategies and expressions. Results are as follows: (1) JS and IS using apolozise, reason, and fuka in refusal act. (2) IS explain reason clearly in refusal act. Other hand JS using aimai reason. (3) JS used expressions of Apology appropriately according to their Power (hierarchical position), while IS made appropriate use of these expressions according to relative Social Distance. (4) IS used interjection and appelation while JS did not using this strategy in refusal act.